2015
DOI: 10.1111/jphp.12407
|View full text |Cite
|
Sign up to set email alerts
|

Eucalyptol suppresses matrix metalloproteinase-9 expression through an extracellular signal-regulated kinase-dependent nuclear factor-kappa B pathway to exert anti-inflammatory effects in an acute lung inflammation model

Abstract: Thus, eucalyptol may be a potentially important agent in the treatment of pulmonary inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 21 publications
0
34
0
1
Order By: Relevance
“…In our experiment, eucalyptol may have modulated IFN-c-dependent proinflammatory mechanisms. According to some authors, the anti-inflammatory effects of eucalyptol include the reduction of the expression of classic proinflammatory cytokines such as TNF-a and IL-1b in several models of inflammation (Santos et al 2001;Juergens et al 2004;Zhao et al 2014;Kim et al 2015). In a study by Santos et al (2001), eucalyptol improved D-galactosamine/lipopolysaccharide-induced liver injury by reducing TNF-c levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experiment, eucalyptol may have modulated IFN-c-dependent proinflammatory mechanisms. According to some authors, the anti-inflammatory effects of eucalyptol include the reduction of the expression of classic proinflammatory cytokines such as TNF-a and IL-1b in several models of inflammation (Santos et al 2001;Juergens et al 2004;Zhao et al 2014;Kim et al 2015). In a study by Santos et al (2001), eucalyptol improved D-galactosamine/lipopolysaccharide-induced liver injury by reducing TNF-c levels.…”
Section: Resultsmentioning
confidence: 99%
“…Its therapeutic role in inflammatory respiratory diseases, such as asthma and chronic obstructive pulmonary disease (COPD), is well established. The effect is associated with the anti-inflammatory (Kim et al 2015) and antioxidant (Rocha Caldas et al 2015) properties of eucalyptol, as shown by a number of preclinical studies. Another recent clinical study demonstrated the long-term benefits of treatment with eucalyptol in COPD prevention and asthma control (Juergens 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Eucalyptol is widely used as a treatment option for symptoms of the common cold, respiratory infections, pancreatitis, and colitis and for pain relief (Juergens, ; Seol & Kim, ). Studies have demonstrated that eucalyptol possess antioxidant activity, can suppress LPS‐induced IL‐1β and NO production, and reduce LPS‐induced NF‐κB activation (Kennedy‐Feitosa et al, ; Kim, Lee, & Seol, ; Li et al, ; Seol & Kim, ). Eucalyptol also inhibits TRPA1 channels and diminishes pain elicited by application of TRPA1 channel agonists to human skin (Takaishi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that eucalyptol may also engage targets in the immune system (Juergens, ). Eucalyptol interfered with arachidonic acid metabolism in blood monocytes of asthma patients, inhibited LPS‐induced IL‐1β production in human monocytes, suppressed LPS‐induced production of nitric oxide in a macrophage cell line and diminished LPS‐induced expression, translocation and transcriptional activities of early growth response factor 1 and NF‐κB in human cell lines (Juergens et al, ,b; Zhou et al, ; Kim et al, ). Finally, eucalyptol also has antioxidant and antimicrobial activity that may contribute to its anti‐inflammatory effects in some pathological conditions (Keinan et al, ; Hendry et al, ; Sadlon and Lamson, ; Greiner et al, ).…”
Section: Introductionmentioning
confidence: 99%